2015
DOI: 10.1080/07421222.2014.1001270
|View full text |Cite
|
Sign up to set email alerts
|

Enticing and Engaging Consumers via Online Product Presentations: The Effects of Restricted Interaction Design

Abstract: and assistant dean (graduate studies) in the School of Computing. He received his Ph.D. in management information systems from University of British Columbia. His research interests include social media, electronic commerce, human-computer interaction, and information privacy. His work has been published in top information systems journals, such as MIS Quarterly, Information Systems Research, and Journal of Management Information Systems, and top human-computer interaction conferences, such as CHI. He has serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 82 publications
(138 reference statements)
0
31
0
1
Order By: Relevance
“…We found that the effects of context-specific variables on customer engagement have been consistently examined. A majority of studies on customer engagement have been conducted in the context of online brand communities and examined how different community-specific characteristics shaped customer engagement in such landscapes (e.g., Chan et al, 2014;Hammedi et al, 2015;Li et al, 2014;Yi et al, 2015;Zhang et al, 2015). For instance, community-specific characteristics, such as community value (Chan et al, 2014), sense of community (Zhang et al, 2015), and trust in a community (Hammedi et al, 2015), were found to positively influence customer engagement in online brand communities.…”
Section: Customer Engagementmentioning
confidence: 99%
“…We found that the effects of context-specific variables on customer engagement have been consistently examined. A majority of studies on customer engagement have been conducted in the context of online brand communities and examined how different community-specific characteristics shaped customer engagement in such landscapes (e.g., Chan et al, 2014;Hammedi et al, 2015;Li et al, 2014;Yi et al, 2015;Zhang et al, 2015). For instance, community-specific characteristics, such as community value (Chan et al, 2014), sense of community (Zhang et al, 2015), and trust in a community (Hammedi et al, 2015), were found to positively influence customer engagement in online brand communities.…”
Section: Customer Engagementmentioning
confidence: 99%
“…They yearn for objects or experiences that make them feel autonomous. In the online gaming environment, a sense of autonomy has been shown to engulf players with feelings of elation and enjoyment as they teleport to a virtual world [87]. If an object or experience fulfills people's need for autonomy, it becomes seamlessly part of and in close proximity to their self.…”
Section: Antecedents Of Prominencementioning
confidence: 99%
“…High perceived serendipity of a product search experience implies that users may encounter interesting and valuable findings that are beyond their expectations. Studies suggest that people enjoy and remain highly engaged in a search experience as they discover new items and new directions that would not have been otherwise considered (Foster and Ford 2003, Sun et al 2013, Yi et al 2015. They are likely to view such a process as creative and fulfilling and thus the chance of regretting the final choice is lower.…”
Section: The Effects Of Search Experience On Decision Satisfactionmentioning
confidence: 99%